Picnic. - Inge, William; Heflin, Julia Dorn.; Inge, William (1965)
Mount Vernon Junior College Curtain Callers present "Picnic," the Pulitzer Prize winner, by William Inge, faculty director: Mrs. Julia Dorn Heflin.
Lloyd Hall, May 6 and 7, 1965.
Title devised by Library staff.
Cast: Margaret Holt Coleman, Jay Ryan, Charla Hayen, Hank Doyle, JoEllen Kennevan, Judith Buck, Martha Wadsworth, Peter Lyons, Katherine Rowell, Leah Murr, Chris Stoll.